2020
DOI: 10.1099/mic.0.000913
|View full text |Cite
|
Sign up to set email alerts
|

A response regulator protein with antar domain, AvnR, in Acinetobacter baumannii ATCC 17978 impacts its virulence and amino acid metabolism

Abstract: Acinetobacter baumannii, a Gram-negative coccobacillus, is notorious for its involvement in opportunistic infections around the world. Its resistance to antibiotics makes treatment of infections challenging. In this study, we describe a novel response regulator protein, AvnR (A1S_2006) that regulates virulence-related traits in Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Variations include those originally designed in P. aeruginosa and Burkholderia spp. The methods of Choi and Schweizer have been adapted for use in A. baumannii (De Silva and Kumar, 2018;De Silva et al, 2020) and includes the initial step of Splicing Overlap Extension (SOE), which introduces an antibiotic resistance gene flanked by Flp Recombinase Target (FRT) sites into the flanking homologous regions of the target gene to allow for selection of recombinants and antibiotic gene removal, respectively (Choi and Schweizer, 2005). Applications in clinical isolates using this method ( Supplementary Table 1) have been successful depending on the type of selection and counter-selection markers used (Trebosc et al, 2016(Trebosc et al, , 2019Xu Q. et al, 2019).…”
Section: Gene Deletion Strategies Using Suicide Plasmidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Variations include those originally designed in P. aeruginosa and Burkholderia spp. The methods of Choi and Schweizer have been adapted for use in A. baumannii (De Silva and Kumar, 2018;De Silva et al, 2020) and includes the initial step of Splicing Overlap Extension (SOE), which introduces an antibiotic resistance gene flanked by Flp Recombinase Target (FRT) sites into the flanking homologous regions of the target gene to allow for selection of recombinants and antibiotic gene removal, respectively (Choi and Schweizer, 2005). Applications in clinical isolates using this method ( Supplementary Table 1) have been successful depending on the type of selection and counter-selection markers used (Trebosc et al, 2016(Trebosc et al, , 2019Xu Q. et al, 2019).…”
Section: Gene Deletion Strategies Using Suicide Plasmidsmentioning
confidence: 99%
“…There are a variety of iterations of this system including various selection markers, and induction parameters (Supplementary Table 3). Versatility of this system has been shown by its successful use in AB5075 (Pérez-Varela et al, 2020;Williams et al, 2020) as well in the clinical isolates AB030, AB031, and LAC-4 with the chromosomal insertion of constitutive fluorescent markers ( Supplementary Table 4) including mTurquoise, RubyRed, mCherry, and sfGFP (Ducas-Mowchun et al, 2019), as well as complementation of deletion mutants in ATCC R 17978 TM using the gentamicin selectable marker (De Silva et al, 2020). The antibiotic selection marker is removed via the Flp recombinase method described above ( Figure 2C) using pFLP2 derivatives (Supplementary Table 2).…”
Section: Single Copy Insertion Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that ANTAR proteins, upon activation (through phosphorylation) bind to their target-RNAs and regulate downstream gene expression in cis (Ramesh et al 2012;Fox et al 2009;Wilson et al 1996a;Chai and Stewart 1998;Mehta et al 2020;Malaka De Silva et al 2020;Weber et al 2019). Hence we analyzed the genomic locations and contexts of the predicted RNAs.…”
Section: Antar-target Rnas Are Located In Untranslated and Coding Regmentioning
confidence: 99%
“…We next asked what cellular processes are linked to ANTAR in actinobacteria. Studies in Enterococcus, Pseudomonas, Klebsiella, Acinetobacter and Geobacter reveal that ANTAR-target RNAs are linked to nitrogen utilization (Ramesh et al 2012;Drew and Lowe 1989;Chai and Stewart 1998;Malaka De Silva et al 2020). Only few studies in actinobacteria have investigated the role of ANTAR.…”
Section: Cellular Pathways and Genes Associated With Actinobacterial mentioning
confidence: 99%